Digital Asset Management Content Architectures, Project Management, and Creating Order out of Media Chaos - Keathley, Elizabeth; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Digital Asset Management: Content Architectures, Project Management, and Creating Order out of Media Chaos is for those who are planning a digital asset management system or interested in becoming digital asset managers. This book explains both the purpose of digital asset management systems and why an organization might need one. The text then walks readers step-by-step through the concerns involved in selecting, staffing, and maintaining a DAM. This book is dedicated to providing you with a solid base in the common concerns, both legal and technical, in launching a complex DAM capable of providing visual search results and workflow options. Containing sample job models, case studies, return on investment models, and quotes from many top digital asset managers, this book provides a detailed resource for the vocabulary and procedures associated with digital asset management. It can even serve as a field guide for system and implementation requirements you may need to consider. This book is not dedicated to the purchase or launch of a DAM; instead it is filled with the information you need in order to examine digital asset management and the challenges presented by the management of visual assets, user rights, and branded materials. It will guide you through justifying the cost for deploying a DAM and how to plan for growth of the system in the future. This book provides the most useful information to those who find themselves in the bewildering position of formulating access control lists, auditing metadata, and consolidating information silos into a very new sort of workplace management tool – the DAM. The author, Elizabeth Ferguson Keathley, is a board member of the DAM Foundation and has chaired both the Human Resources and Education committees. Currently Elizabeth is working with the University of British Columbia and the DAM Foundation to establish the first official certificate program for Digital Asset Managers. She has written, taught, and been actively a part of conferences related to the arrangement, description, preservation and access of information for over ten years. Her ongoing exploration of digital asset management and its relationship to user needs can be followed at her homepage for Atlanta Metadata Authority : atlantametadata.com.
Keywords: Application software; Natural language processing (Computer science).; Computer Applications; Computer Appl. in Administrative Data Processing; Natural Language Processing (NLP).